Thermally stable carbon-coated SiC/polydimethylsiloxane nanocomposites for EMI shielding in the terahertz range. (September 2022) - Huang, Feirong; Fan, Shuting; Tian, Yuqi; Qu, Xinghao; Li, Xiyang; Javid, Muhammad; Zhang, Xuefeng; Zhang, Zhidong; Dong, Xinglong; Cao, Tun; Park, Sung Jin
Highlights: Nanocomposites are developed as high-performance THz shielding materials. Thermal stability of nanocomposites improves by increasing filler content. Nanocomposites have shielding and absorption performances in a wide frequency range. Performances of nanocomposites improve by increasing filler content and thickness. Abstract: Rapid development of terahertz (THz) technologies makes electromagnetic interference (EMI) shielding increasingly critical for control of electromagnetic (EM) radiation and reduction of EM pollution. In this study, carbon-coated silicon carbide nanoparticles (SiC@C NPs) are synthesized by arc-discharge plasma and dispersed into a polydimethylsiloxane (PDMS) matrix to fabricate SiC@C/PDMS nanocomposites (SiC@C/PDMS NCs). The NCs demonstrate excellent THz shielding/absorption performances in virtue of the SiC@C NP fillers and composite structure in a wide range from 0.5 to 3.0 THz. The maximum shielding efficiency and reflection loss in the range from 0.5 to 3.0 THz reach up to 44.5 and 19.0 dB on average, respectively, for the NC with a loading of 10 wt.% SiC@C NPs and 0.6 mm thickness. The SiC@C/PDMS NCs possess a high thermal stability in air, as well as lightweight and hydrophobicity. This work would provide an insight into the functionalization of the SiC@C NPs as high-performance THz shielding materials. Graphical abstract: Image, graphical abstract